Presidential elections ordered for 10 May 2020 in the light of the draft resolution of the Sejm of Republic of Poland on the appointment of a commission of inquiry - Szmyt, Andrzej (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The study is devoted to the analysis of the draft resolution of the Sejm of Republic of Poland on the appointment of a commission of inquiry on the elections for President of the Republic of Poland ordered for 10 May 2020. The elections did not take place on this date. There were significant violations of the law by government bodies in the run-up elections. There were also multimillion looses. Therefore, opposition MPs have submitted a draft resolution to set up a Sejm committee of inquiry to revise the matter.